Digitalization as a Driver of ASEAN Inclusivity After the Global Pandemic - Hanuzulia Rahtio (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Digitalization has been a key driver of inclusiveness in ASEAN post-global pandemic. Through the use of digital technology, countries in ASEAN can improve accessibility and connectivity for all people, especially for marginalized communities. Through digitalization initiatives, the education, health, and economic sectors can provide more affordable and efficient services to the entire ASEAN population. In addition, digitalization also enables the creation of new jobs and economic progress that is evenly distributed throughout the ASEAN region. However, the challenges that need to be overcome are limited digital infrastructure and inequality of internet access that still exists in some regions.